Carbohydrate‐Based Electron Donor for Biological Nitrate and Perchlorate Removal From Drinking Water. Issue 12 (1st December 2015) - Upadhyaya, Giridhar; Kotlarz, Nadine; Togna, Paul; Raskin, Lutgarde
Abstract : This study evaluated the feasibility of replacing acetic acid with a commercial carbohydrate‐based electron donor (CBED) for removal of nitrate and perchlorate (ClO4 – ) from drinking water. Bench‐scale biologically active carbon fixed‐bed and fluidized‐bed reactors (FXBR and FLBR, respectively), with an initial empty bed contact time (EBCT) of 42.8 min, were fed simulated groundwater containing 15 mg/L nitrate as nitrogen and 200 μg/L ClO4 – . EBCT in the FLBR after final expansion was 80.5 min. During the first 100 days using acetic acid at 125 mg/L chemical oxygen demand (COD), complete nitrate removal was achieved in both systems, whereas perchlorate in the FXBR and FLBR effluents remained below 3 and 6 μg/L ClO4 –, respectively. For comparable removals, influent COD requirement was higher with the CBED. Biomass yields with acetic acid and the CBED were 0.54–0.58 and 0.59–0.74 mg CODbiomass /mg CODsubstrate, respectively. The higher yield with the CBED resulted in more frequent maintenance requirements.